Perancangan sistem manajemen session real-time menggunakan firestore, python, dan javascript - Richard Alvin Munandar; Pratyaksa Ocsa Nugraha Saian (Fakultas Teknologi Informasi, Universitas Kristen Satya Wacana, 2026)
PT. XYZ is one of the largest retail companies in Indonesia. PT. XYZ has a website-based application that functions to help employees who work in IT Support to handle operational problems. However, this website has not implemented a session management system which can affect the level of security. Therefore, a system design was created for real-time session management using Firestore, Python, and Javascript. Firestore is used as a database to store sessions and Firestore has a feature called the Firestore snapshot listener which functions to detect changes in real-time. The research method includes identifying needs, initial prototype design, prototype creation, prototype evaluation, prototype refinement, and system implementation. Black Box Testing is used as a method for testing this system, where the results are in accordance with the needs and interviews are conducted with the admin of this website to test the session management system and find out the admin's response regarding the designed session management system. The results obtained are satisfactory because security can be further improved, user experience is improved, and the company's needs can be achieved.